2020
DOI: 10.1038/s41398-020-0767-0
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal vagal complex and hypothalamic glia differentially respond to leptin and energy balance dysregulation

Abstract: Previous studies identify a role for hypothalamic glia in energy balance regulation; however, a narrow hypothalamic focus provides an incomplete understanding of how glia throughout the brain respond to and regulate energy homeostasis. We examined the responses of glia in the dorsal vagal complex (DVC) to the adipokine leptin and high fat diet-induced obesity. DVC astrocytes functionally express the leptin receptor; in vivo pharmacological studies suggest that DVC astrocytes partly mediate the anorectic effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 79 publications
1
29
1
Order By: Relevance
“…One of these, FABP7, has been proposed to function in glial cells within the ARC to impair leptin signaling especially on HFD 34 . Several studies demonstrated a key role of glial cells on leptin and feeding regulation by the hypothalamus [53][54][55][56][57][58] .…”
Section: Discussionmentioning
confidence: 99%
“…One of these, FABP7, has been proposed to function in glial cells within the ARC to impair leptin signaling especially on HFD 34 . Several studies demonstrated a key role of glial cells on leptin and feeding regulation by the hypothalamus [53][54][55][56][57][58] .…”
Section: Discussionmentioning
confidence: 99%
“…46 In addition, studies carried out on rats have highlighted that that DVC astrocytes partly mediate the anorectic effects of leptin and pharmacological glucagonlike peptide-1 receptor ligands. 47,48 Overall, these findings suggest that NTS astrocytes are involved in the integration of peripheral satiety signals to control feeding behaviour.…”
Section: Box 2 Astrocytes As Gatekeepers For Energy Homeostasismentioning
confidence: 78%
“…Because ventilation must parallel energy expenditure for arterial blood gas homeostasis, there must be areas of the CNS in which the circuitry controlling these two systems converge. NTS LepRb neurons and glia contribute to interactions of energy balance with gastrointestinal (GI) satiation signaling (Myers et al, 2009;Hayes et al, 2010;Stein et al, 2020). Because the NTS is also a major chemosensitive area that regulates breathing (Nattie, 2001;Huda et al, 2012), it appears ideally suited to harmonize these multiple functions with body-mass-related respiratory control and CO 2 chemosensitivity.…”
Section: Discussionmentioning
confidence: 99%